Atomistic Modelling of Nitrogen-rich Biobased Carbon Materials - ANNA HERRERA (2024)
Chars from pyrolysis and hydrothermal processing of biomass are potential waste-to-material valorisation candidates for being a heteroatom-rich and porous carbon materials. They are suitable as electrodes in energy storage, and as biobased fertilisers in soil amendments. In energy storage, biomass’ heteroatoms are incorporated into the electrode’s structure, increasing wettability, and promoting electrode-electrolyte interactions. In agriculture, nitrogen functionalities and high porosity allow for essential elements adsorption and water retention, therefore enhancing the plant uptake. This thesis uses atomistic modelling of char graphitic surfaces (both ﬁnite and periodic) with diﬀerent surface features and performs density functional theory calculations to achieve a better understanding of the interactions between biobased chars and relevant adsorbates in energy storage and soil remediation. The eﬀect of diﬀerent nitrogen functional groups in the graphitic structure was investigated, along with the eﬀect of surface curvature and radius, and the eﬀect of spin multiplicity of certain transition metal species.The methodology and codes developed in this thesis should allow the study of any adsorption system provided a surface and an adsorbate. The results indicate that the interactions between species and biobased chars strongly depend on the surface curvature and nitrogen content – but also on the spin multiplicity of the transition metal species, which in most cases evolves into an open shell electronic structure to maximise coordination with the aromatic system. The ﬁndings provide additional fundamental knowledge to help with the development of ﬁt-for-purpose biobased chars for energy storage with a tailored nanostructure, and biobased fertilisers, among other potential applications. Based on this ﬁndings, processing conditions can be selected to promote those chemical and structural features highlighted by the theoretical studies presented here.